2018
DOI: 10.1128/iai.00530-18
|View full text |Cite
|
Sign up to set email alerts
|

Dextran Sulfate Sodium Colitis Facilitates Colonization with Shiga Toxin-Producing Escherichia coli: a Novel Murine Model for the Study of Shiga Toxicosis

Abstract: Shiga toxin-producing (STEC) are globally important gastrointestinal pathogens causing hemorrhagic gastroenteritis with variable progression to potentially fatal Shiga toxicosis. Little is known about potential effects ofderived Shiga-like toxins on host gastrointestinal immune responses during infection in part due to lack of a reproducible, immunocompetent animal model of STEC infection without depleting the commensal microbiota.Here we describe a novel and reproducible murine model utilizing dextran sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Several reports have revealed that the relative abundance of E. coli increases as a result of inflammation of the intestinal tract [73][74][75][76]. Furthermore, DSS treatment was shown to promote colonization with Shiga toxin-producing E. coli [77]. Notably, in our study, the relative abundance of E. coli was observed to be lower in the DSS + CD + PWS group than in both the DSS and DSS + CD groups.…”
Section: Discussionsupporting
confidence: 46%
“…Several reports have revealed that the relative abundance of E. coli increases as a result of inflammation of the intestinal tract [73][74][75][76]. Furthermore, DSS treatment was shown to promote colonization with Shiga toxin-producing E. coli [77]. Notably, in our study, the relative abundance of E. coli was observed to be lower in the DSS + CD + PWS group than in both the DSS and DSS + CD groups.…”
Section: Discussionsupporting
confidence: 46%
“…6B; note that this was also the case for the 112648 strain and its mutants). Then, using germ-free mice treated with dextran sulfate sodium (DSS), which induces colitis [40], we evaluated the virulence of the WT 12E129 strain and its mutants carrying either CI-4 or CI-5 L-Stx2a phage. A 12E129 mutant lacking both phages was also generated and used as a negative control after confirming that it produced no Stx2 (dKO in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Mice that were fed a high fiber diet (HFD) exhibited a decrease in native Escherichia species and increased colonization of STEC, weight loss, and mortality compared with mice that were fed a low fiber diet (LFD) [45]. A colitis murine model generated using dextran sulfate sodium similarly had an increased risk of STEC infection [46]. These reports indicate that the robustness of the gut microbiota plays an important role in the defense against STEC infection (Figure 2).…”
Section: Crosstalk With Gut Microbiota In Intestinal Pathology Upon S...mentioning
confidence: 99%